2023
DOI: 10.3390/technologies11020062
|View full text |Cite
|
Sign up to set email alerts
|

Geographical Dependence of Open Hardware Optimization: Case Study of Solar Photovoltaic Racking

Abstract: Open-source technological development is well-known for rapid innovation and providing opportunities to reduce costs and thus increase accessibility for a wide range of products. This is done through distributed manufacturing, in which products are produced close to end users. There is anecdotal evidence that these opportunities are heavily geographically dependent, with some locations unable to acquire components to build open hardware at accessible prices because of trade restrictions, tariffs, taxes, or mar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 83 publications
0
4
0
Order By: Relevance
“…Furthermore, the final costs of these systems are subject to change based on the cost of lumber at the time of purchase and where the material is being purchased [76]. A sensitivity analysis is provided on both commodity wood pricing and location to provide a range of final costs and costs per W of each system.…”
Section: Economic Analysismentioning
confidence: 99%
See 3 more Smart Citations
“…Furthermore, the final costs of these systems are subject to change based on the cost of lumber at the time of purchase and where the material is being purchased [76]. A sensitivity analysis is provided on both commodity wood pricing and location to provide a range of final costs and costs per W of each system.…”
Section: Economic Analysismentioning
confidence: 99%
“…In the extreme case, such as Cape Race, Newfoundland, where the wind load is more than double that of typical urban cities, this system becomes challenging. The applicability of these systems worldwide [76], much like in Canada, is dependent on the calculated wind load, and the individual's decision in deeming if the build is feasible based on the cost of rocks associated with this wind speed. As shown in the Appendices, the distance to the center of the modules, d, has a direct correlation to increasing the price.…”
Section: Economic Analysismentioning
confidence: 99%
See 2 more Smart Citations
“…Wood has already been shown to be a cost-effective racking material for fixed tilt [20], variable tilt [27], vertical PV [28] and awning designs [86]. Previous work has shown that the economics of wood vs aluminum racks varies widely by geography [87], but it is superior in most of North America.…”
Section: Selection Of Material: Woodmentioning
confidence: 99%